2020
DOI: 10.3390/ijms21217928
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Relevance of HJURP Expression in Patients with Surgically Resected Colorectal Cancer

Abstract: HJURP is a key factor for CENP-A deposition and maintenance in centromeres. The role of mis-regulation of histone chaperones in cancer initiation and progression has been studied. However, its role in colorectal cancer is still unclear. In this study, we aimed to evaluate the expression of HJURP in 162 colorectal cancer tissue. To investigate the function of HJURP in the colorectal cancer cell, we suppressed HJURP expression by siRNA and confirmed proliferation, migration, invasion, and anchorage independent o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 21 publications
1
26
0
Order By: Relevance
“…In addition, in hepatocellular carcinoma 12 , 26 , HJURP is also stained in the cytoplasm. However, in pancreatic cancer 27 and colorectal cancer 28 , its localization is mainly in the nucleus. In glioma 29 , HJURP is stained in both cytoplasm and nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in hepatocellular carcinoma 12 , 26 , HJURP is also stained in the cytoplasm. However, in pancreatic cancer 27 and colorectal cancer 28 , its localization is mainly in the nucleus. In glioma 29 , HJURP is stained in both cytoplasm and nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by M Miyo, the proliferation of SW480 cells was reduced compared with HCT116 cells, but the migration capacity was increased [ 53 ]. In another study, the proliferation of SW620 and SW480 cells was lower than that of HCT116 and HT29 cells, but the migration and invasion abilities were increased compared with HCT116 and HT29 cells [ 54 ]. These findings indicated that different tumour cell lines may have different proliferation and tumourigenesis mechanisms, which may partially be explained by the enrichment and loss of biological phenotypes in the process of establishing different cell lines and might also be related to the different donor sources.…”
Section: Discussionmentioning
confidence: 99%
“…HJURP knockdown suppressed the migration and invasion of NSCLC cells via inhibition of the activation of Wnt/β-catenin signaling ( Wei et al, 2019 ). Similarly, ectopic expression of HJURP can promote proliferation, migration, and invasion of other tumor cells ( Chen T. et al, 2018 , 2019 ; Kang et al, 2020 ). Furthermore, high expression of HJURP is associated with poor prognosis in patients with colorectal and ovarian cancer and is an independent prognostic biomarker for those cancers ( Li et al, 2018 ; Kang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%